Customer Feedback Analysis Applying the RFC Model Hybrid Sentiment Extraction and Contrast Dictionary - Myint Zaw (Prince of Songkla University, 2023)
Thesis (Ph.D., Computer Engineering)--Prince of Songkla University, 2021